An experiment process for designing a kinetic wall sculpture through implementation of Malay identity in mass production / Nur Syahirah Adnan, Hanif Khairi and Rusmadiah Anwar - Adnan, Nur Syahirah; Khairi, Hanif; Anwar, Rusmadiah (Universiti Teknologi MARA, 2020)
The study intends to sustain the essential element of Malay identity, which represented the cultural identity of Malays. Malay identity should be appreciated and preserved as it is part of Malay heritage. The development progress of Malaysia brought many benefits but behind the success of Malaysian development, it also gave an impact on Malay culture in the context of identity itself. In this area of research, the implementation of Malay identity is one of the important elements towards discovering the potentials home decoration to be used in modern living space which can be applied to it. The gathering insights of products will be through the pattern and needs. The integration will be happening in a conceptual process which is the study of Malay motif in wood carving, the technical process which is to categorize the types of the kinetic art form that are suitable for wall decoration and lastly develop design criteria based on usability, aesthetic and technically. Therefore, the best solution to preserve the Malay identity is through artwork for example kinetic wall sculpture.